Trace element deficiency is highly prevalent and associated with infection and mortality in patients with alcoholic hepatitis. Issue 3 (23rd June 2020) - Dhanda, Ashwin; Atkinson, Stephen; Vergis, Nikhil; Enki, Doyo; Fisher, Andrew; Clough, Robert; Cramp, Matthew; Thursz, Mark
Summary: Background: Malnutrition is common in patients with alcohol‐related liver disease and is associated with outcome in patients with alcoholic hepatitis. Trace elements (cobalt, copper, iron, selenium and zinc) are micronutrients essential for many cellular processes including antioxidant pathways. The prevalence and relevance of trace element deficiency is unknown in alcoholic hepatitis. Aim: To determine the prevalence of trace element deficiency and its association with clinical outcomes in patients with alcoholic hepatitis. Methods: Serum was obtained from patients with alcoholic hepatitis, alcohol‐related cirrhosis and healthy volunteers as part of clinical trials, cohort studies and a biobank. Trace element concentration was measured by inductively coupled plasma mass spectrometry. Association of trace element levels with development of infection within 90 days and mortality within 28 and 90 days was evaluated by multivariate logistic regression. Results: Sera from 302 patients with alcoholic hepatitis, 46 with alcohol‐related cirrhosis and 15 healthy controls were analysed for trace element concentration. The prevalence of zinc deficiency (85%) and selenium deficiency (67%) in alcoholic hepatitis was higher than in alcohol‐related cirrhosis (72% [p=0.04] and 37% [p<0.001], respectively). Zinc, selenium, copper and chromium were significantly different between groups. Iron deficiency was a predictor of development of infection within 90 days. Zinc deficiency was a predictor of mortality within 28 and 90 days. Conclusion: Trace element deficiency in patients with alcoholic hepatitis is highly prevalent and associated with infection and mortality. Supplementation with selected trace elements may improve clinical outcomes in this patient group but further insight is required of their biological and clinical effects.